KLAUSA NON-FINIT DALAM NOVEL â€œAT FIRST SIGHTâ€ KARYA NICHOLAS SPARKS - TENDEAN, ELRICK RICKO (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACT A non-finite clause is a dependent or an embedded clause. This clause is divided into infinitive clause, -ing participle clause and â€“ed participle clause. A non-finite clause serves as a subject, direct object, subject attribute, object attribute, predicator complement and adverbial in the structure of the sentence. The aims of this research are to identify and classify the types of non-finite clause, and to analyze structurally the function and category of non-finite clause in the novel â€œAt First Sightâ€. The method used in this research is descriptive method. The collected data are identified, classified and analyzed by using the theory of Aarts and Aarts (1982).Â  There are 750 non-finite clauses found in the novel from chapter one to chapter ten. They are divided into three types ; 432 infinitive clauses, 304 â€“ing participle clauses and fourteen â€“ed participle clauses (included twelve non-finite clauses as a subject, fifty four non-finite clauses as a direct object, eight non-finite clauses as a subject attribute, six non-finite clauses as an object attribute, 247 non-finite clauses asÂ  a predicator complement and ninety three non-finite clause as an adverbial). Â Keywords : Clause, analysis, Structure